Essential components of teamwork and service to internal and external clients - Rosales Castillo, Luis Roberto (2010)
The article analyzes a series of basic components for customer service from a marketing point of view. It begins with the explanation of several characteristics that are required for a company to crystallize the teamwork that, in the end, will provide the success or failure of that company. These characteristics are: work relationship, cooperation, companionship, communication, motivation and leadership. Subsequently, the article presents a section that examines human relations and conflict management in organizations, emphasizing the attitudes, aptitudes and types of personalities that human beings manifest as part of their essence. Finally, this text includes a section that highlights concepts related to customer service and sales techniques that exist today.